Récits de vie de réfugiés. Une présentation du fonds d’archives de l’Association pour les Victimes de la Répression en Exil - Isabelle Lacoue-Labarthe (Diasporas: Circulations, Migrations, Histoire)
In 1985, the Association for the Victims of Repression in Exile (Association pour les Victimes de la Répression en Exil/AVRE) was created by a Doctor, Hélène Jaffé. She was determined to open a centre to care for torture victims given the absence of any such facility in France at that time. Until its closure in 2007, AVRE was a place where refugees’ stories were collected, whether in the form of spontaneous oral accounts or written narratives addressed to the French Office for the Protection of Refugees and Stateless Persons (Office Français de Protection des Réfugiés et Apatrides/OFPRA). This article presents some of these documents and points to their notable value in writing the history of diasporas, and migrations more generally, when used in conjunction with other sources.